2020
DOI: 10.26452/ijrps.v11i4.3221
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer activity of ylang-ylang essential oil in Ehrlich Ascites Carcinoma cell-treated mice

Abstract: Essential oils are secondary metabolites contains a complex mixture of with a diverse array of chemical structures, play a crucial role in the management of complex diseases like cancer via synergistic and antagonism effect. essential oil (YYEO) extracted from the flowers of Cananga is renowned forits fragrance, contained more than 150 essential components within it, and utilized in various diseases and cosmetics. Traditionally YYEO is being used as an aphrodisiac, , , antiseptic, in food and beverages as a fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(18 reference statements)
0
0
0
Order By: Relevance
“…Previous studies have reported the antitumor activity of Y-oil against hepatocarcinoma [21], MCF-7 and MDA-MB-231 human breast tumor cell lines [49,50], and Ehrlich Ascites Carcinoma-treated mice model [51]. The anticancer activities of Y-oil are attributed to the high contents of diethyl phthalate ester (29.08%) and sesquiterpenes hydrocarbons (27.33%), as identified by the GC-MS analysis.…”
Section: Cytotoxicity (Srb Assay)mentioning
confidence: 97%
“…Previous studies have reported the antitumor activity of Y-oil against hepatocarcinoma [21], MCF-7 and MDA-MB-231 human breast tumor cell lines [49,50], and Ehrlich Ascites Carcinoma-treated mice model [51]. The anticancer activities of Y-oil are attributed to the high contents of diethyl phthalate ester (29.08%) and sesquiterpenes hydrocarbons (27.33%), as identified by the GC-MS analysis.…”
Section: Cytotoxicity (Srb Assay)mentioning
confidence: 97%
“…In previous studies, thirteen alkaloids and twenty terpenoids were identified from the stem (15). C. odorata showed a potent cytotoxic effect against hepatocellular carcinoma cancer cell lines, HepG2, and Hep2.2.15 (16), anti-cancer activity in EAC treated mice (17), and exhibited anti-inflammatory effect (18). The in vivo and in vitro evaluation of Liriodenine, an alkaloid isolated from C. odorata showed potent inhibitory activity against topoisomerase II (19).…”
Section: Introductionmentioning
confidence: 99%